Penguatan Karakter Disiplin Santri sebagai Strategi Pengembangan SDM Pesantren melalui Program Pelatihan Santri Teladan - Fahrudin, Arif; Suharno; Rosid Ridlo; Harun Joko Prayitno; Indri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the process of internalizing disciplinary character through the Santri Teladan (Exemplary Student) Training Program at Pondok Pesantren Modern Muhammadiyah Sangen, as well as to examine its supporting and inhibiting factors. The primary issue addressed is that discipline cultivation often remains a mere formality and has not fully fostered deep value awareness. A qualitative approach with a case study design was employed in this research. The participants included program managers, instructors (ustaz), supervisors (musyrif), and participating students (santri), selected through purposive and snowball sampling techniques. Data were collected via semi-structured interviews, participant observation, and documentary studies, and subsequently analyzed using the Miles and Huberman interactive model. The main findings reveal that the internalization of disciplinary character is executed systematically through integrated classical learning on caregiving, teaching, and preaching (da'wah), reinforced by daily routines (such as morning assemblies and attendance checks), close supervision, and field training. This process successfully nurtures disciplinary awareness, mental readiness, and social responsibility among students. The program's success is driven by high student motivation and practitioner involvement, despite challenges like physical exhaustion due to a rigorous schedule and hot weather. These findings contribute to strengthening Muhaimin's value internalization theory (value transformation, transaction, and trans-internalization) within the context of structured boarding school training programs. In conclusion, an experiential field-based training program is highly effective in driving behavioral transformation and cultivating spiritual-managerial consciousness in students. Practically, this model provides a viable reference for other Islamic boarding schools to design contextual character development programs. Future research is recommended to utilize a longitudinal approach or expand the scope to include schools with different institutional characteristics.